Epidemiological risk factors and phylogenetic affinities of Sarcocystis infecting village chickens and pigs in Peninsular Malaysia - Sabrina, D.L.; Latiffah, H.; Reuben, S.K.S.; Ooi, P.T. (Malaysian Society of Parasitology and Tropical Medicine, 2023)
The intake of food and water containing the Sarcocystis parasite has been linked to a number of outbreaks worldwide, including Malaysia. Nevertheless, the lack of surveys and epidemiological data on Sarcocystis infections in Malaysia makes it difficult to estimate its occurrence in humans and animals. A cross-sectional study was conducted to determine the prevalence of Sarcocystis and the risk factors associated with infection among village chickens and pigs reared under different farm managements in Peninsular Malaysia. Phylogenetic trees were constructed using partial fragments of the 18S rRNA gene and ITS1 sequences. In the present study, 680 sera samples were collected from village chickens (n=250) and commercial pigs (n=433) and anti-Sarcocystis antibodies were screened using the enzymelinked immunosorbent assays (ELISA) kit. At the animal level, the prevalence of Sarcocystis was 9.2 (95 CI: 5.92-13.48) and at the farm level, it was 64.0 (95 CI: 42.52-82.03) in village chickens. The animal-level seroprevalence of Sarcocystis for pigs was 3.7 (95 CI: 2.13-5.93) and 36.8 (95 CI: 16.29-61.64) at the farm-level. Polymerase Chain Reaction (PCR) was conducted on meat samples from various parts of village chickens (n=250) consisting of brain, heart, lung, and pectoralis muscle tissues, and pork (n=121) consisting of intercostal muscle, diaphragm, and tongue. Sarcocystis DNA was detected in 6.4 (95 CI: 4.60-11.60) of village chicken samples but zero in pork samples. A total of 11 unique Sarcocystis haplotypes were isolated from these tissue samples. Multivariable logistic regression analysis of the putative risk factors showed a statistically significant association between Sarcocystis infection in pigs and uncovered storage of feed. Although no zoonotic Sarcocystis was isolated in this study, we reported the first discovery of S. wenzeli in Malaysia.